HAMBATAN SISWA DALAM MENYELESAIKAN SOAL BENTUK PANGKAT BERDASARKAN KRITERIA KESALAHAN WATSON DI SMA - Akwila Nuban; Sugiatno Sugiatno; Asep Nursangaji (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
AbstractThis research aims to find out and describe the learning obstacles experienced by students in solving math problems in SMA Negeri 7 Pontianak. The intended learning obstacles are epistemological obstacles. Learning obstacles experienced by students are seen when students solve problems. Mistakes made by students in completing problems are grouped into the Watson Error Criteria. After that will be known factors that cause students to experience learning obstacles. The research method used in this research is descriptive method in the form of case study research. Data collection techniques used are direct observation techniques with data collection tools using diagnostic tests in the form of tru-false questions and conducting interviews with students who make mistakes. The subjects in this study were the 10th grade students of Natural Sciences 4 of SMA 7 Pontianak many as 29 students. The results of this study indicate that (1) Types of errors made by students based on the Watson Error Criteria include inappropriate data, inappropriate procedure, omitted conclusion. (2) Students who make mistakes experience epistemological obstacle specifically conceptual obstacle. The conceptual obstacle in question is that students are not able to explain the concept of rank in particular (3) Factors that cause students to experience obstacles in solving problems are social factors. The social factor in question is the human being present and not the human being present in class.Keywords: Criteria Error Of Watson, Epistemology Obstacle, Learning Obstacle